All sail set a romance of the Flying Cloud - Sperry, Armstrong 1897- (Nonpareil book, 1984)
When his father loses his fortune, a boy is taken on by a famous shipbuilder and eventually makes a maiden, record-breaking trip around Cape Horn on the "Flying Cloud."